Behavioral Disorders in Association with Posterior Callosal and Frontal Cerebral Infarction - J. P. Lejeune; D. Caparros-Lefebvre (Behavioural Neurology)
Behavioral disorders were a prominent clinical feature after the surgical treatment of an anterior communicating artery aneurysm rupture in a 44-year-old man. Callosal apraxia was associated with an alien hand. The latter remained 1 year after surgery while diagonistic apraxia disappeared after 3 months. Other callosal signs included left agraphia, tactile anomia and auditory suppression. MRI revealed posterior callosal infarction and a right frontal infarct. The association of diagonistic apraxia and alien hand is rarely reported.